Creative Business Financial Literacy in Yogyakarta - Dwitya Aribawa; Ignatia Ryana Widyatini (International Journal of Social Science and Business, 2017)
Small and medium scale businesses (SMEs) have relatively difficulty in increasing their business scale. Financial literacy is a fundamental factor for economic growth and financial stability. The implementation of the AEC in 2016 shows a shift in global economic competition in South East Asia stressing much on value added economics. Indonesia Creative Economy Agency has projecting the creative economy as one of essential element to foster economic growth and sustainable development through this globalization changes Creativity must be supported by a strong foundation of management to create a competitive advantage in business. There is no research or survey in Indonesia that specifically explore the financial literacy roles for the company, in this study corporate financial literacy can be seen from the point of view of the owner and / or manager of company. Following importance of financial literacy to development of business development, this research aim to explore the important factors that affect as the foundation of financial literacy level of business owners that works on creative sectors in Special District of Yogyakarta areas. The result of this research shown firm demographic, financial fraud intention, firm financial capability and firm financial condition partially and simultaneously influence financial literacy for Yogyakarta creative business. In macro aspect, good financial literacy leads to good financial decision making, this finding found relative vary on individual level studies. In this research, it also infer that low level of financial literacy lead to high degree of fraud intention. This research suggest to policy makers that increase financial literacy level will increase financial inclusion of the country itself. Financial knowledge escalation will effectively done through the synergy of stakeholders, which is government, academia, private sector (small and big firms) and civil society.